The Reuse of Tombs in Eastern Arabia - Döpper, Stephanie (Archaeopress Publishing, 2025)
People in the past were always confronted with surviving remains from previous periods, and reacted to and engaged with them in varying ways. One activity through which this becomes visible is the reuse of tombs. If this reuse is an intentional reference to the past, it explicitly communicates meaning and thus cultural memory. In Eastern Arabia, however, this phenomenon received little attention in archaeological research, often having been discounted by the excavators as a disturbance to the first use of a tomb.This book will investigate reuse of tombs from the beginning of the Early Bronze Age until the end of the Sasanian period in order to understand the underlying purposes and social context of this practice. In Eastern Arabia, where the adding of new burials to the original content of the tomb is common, such reuse might have functioned to make sense of the present, to give orientation in new situations and to help shape a cultural identity. Reuse occurred more often in the Iron Age and Samad/PIR periods than in all other periods investigated, combined. These are also times of visible social hierarchies. The resulting tensions made counter-measures that both promoted social cohesion and group identity and legitimised the role of the elites necessary. This might have been achieved through creating cultural memory by reusing old tombs.